2016
DOI: 10.1161/circulationaha.115.016783
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes Mellitus and Prevention of Late Myocardial Infarction After Coronary Stenting in the Randomized Dual Antiplatelet Therapy Study

Abstract: Background— Patients with diabetes mellitus (DM) are at high risk for recurrent ischemic events after coronary stenting. We assessed the effects of continued thienopyridine among patients with DM participating in the Dual Antiplatelet Therapy (DAPT) Study as a prespecified analysis. Methods and Results— After coronary stent placement and 12 months treatment with open-label thienopyridine plus aspirin, 11 648 patients free of ischemic or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 28 publications
(28 reference statements)
1
28
0
1
Order By: Relevance
“…242 However, there was no signal for heterogeneity with respect to the concomitant presence of diabetes mellitus across all other ischaemic or safety endpoints. Finally, no difference with respect to the presence or absence of diabetes was observed for the primary efficacy endpoint in the PEGASUS study (P int = 0.99).…”
Section: Diabetes Mellitusmentioning
confidence: 95%
“…242 However, there was no signal for heterogeneity with respect to the concomitant presence of diabetes mellitus across all other ischaemic or safety endpoints. Finally, no difference with respect to the presence or absence of diabetes was observed for the primary efficacy endpoint in the PEGASUS study (P int = 0.99).…”
Section: Diabetes Mellitusmentioning
confidence: 95%
“…46 The recent dedicated subanalysis of the DAPT trial showed that prolonged DAPT reduced the risk of myocardial infarction, but this benefit was attenuated in patients with diabetes compared with those without diabetes. 47 Similarly, in the DES-LATE, patients with diabetes showed a trend towards benefit from interrupting DAPT at 12 months, although the P value for interaction was borderline (P=0.07). 48 Conversely, other trials, includ-ing OPTIMIZE, 26 RESET, 28 I-LOVE-IT 2, 37 ISAR-SAFE, 38 ARCTIC Interruption, 49 and the recently published IVUS-XPL 40 did not show significant heterogeneity between subgroups with and without diabetes.…”
Section: Diabetes Mellitus and Daptmentioning
confidence: 95%
“…Both presence of diabetes and the degree of diabetic control can affect clopidogrel metabolism, as well as platelet inhibition by clopidogrel (36,37). Benefit from extended DAPT has been shown to be attenuated in patients with diabetes compared with individuals without diabetes mellitus (38). Furthermore, body mass index is often higher among patients with diabetes mellitus and may affect the degree of platelet inhibition by clopidogrel (39,40).…”
Section: Short Vs 12 Monthsmentioning
confidence: 99%